LC-MS/MS Analysis of albendazole and its metabolites in animal tissues - Ana Csuma,; Ana Cismileanu (Medicamentul Veterinar)
Treating the animals with veterinary medicines raise the issue of residues that can persist in their edible tissues. In order to establish the withdrawal time necessary for depletion of the residues to sufficiently low concentration not to affect human health, biological tests performed on animals implicitly involve the use ofsensitive and reliable analytical methods for residues determination.The aim of this work was to establish and validate a sensitive and reliable method for simultaneous determination of albendazole and its metabolites, albendazole sulfoxide, albendazole sulfone and 2-aminoalbendazole sulfone in animal tissues by LC/MS/MS. The method involves acid hydrolysis with 6N HCl in order to release most residues, in particular the bound metabolite 2-amino-albendazole sulfone especially from liver, followed by extraction with ethyl acetate and solid phase clean-up of the extract on a C18 SPE cartridge. The liquid chromatographic separation was achieved on a XTerra MS C18 column (10 cm x 2,1mm, 3,5μm), with gradient elution of 0,1 % formic acid – methanol. Detection was performed by mass spectrometry in ESI+ mode. The limits of quantification were lower than 4 μg/ml for each component. The correlation coefficients (R2) of the calibration curves (in the range from 0,01 μg/ml to 0,5 μg/ml) were higher then 0,9935. The relative standard deviations of repetability on samples naturaly contaminated from treated animals were between 5,75% and 11,6%. Recoveries from fortified muscles in the range of 10 μg/kg to 100 μg/kg were between 70,2% and 88%with relativ standard deviation of 5,4%-12,2%. For liver fortified in the range of 100 μg/kg to 1000 μg/kg recoveries between 70,3% and 83,2% were obtained with relative standard deviation of 5,7%-11%.